Airborne Magnetic Survey and Remote Sensing Applied to Structural Study in Vohilava Area Madagascar - Henri, Razananirina; Raymond, Rakotondrazafy (International Journal of Geography and Geology, 2022)
Mananjary district is known for its gold production. To better understand the gold mineralization distribution, a regional structural study was undertaken using airborne geophysics and remote sensing (RS). Magnetometry data, Landsat Operational Land Imager (OLI) 8 satellite-image and DEM (Digital Elevation Model) have been processed and interpreted. Signals associated with deep structures are weak and dominated by strong signals from surficial magnetic sources. To overcome this problem, local-phase based filters were used. A deep knowledge of each filter allows to use it separately or in combination with other filters. RS is a powerful tool for a regional study. Color composite technique and DEM analysis were helpful to bring out faults and structures. The combination of magnetometry and RS allows geologists to efficiently delineate prospective zones. The study has unveiled a dextral strike-slip fault (SSF) over 240km and associated faults, folds, flower structure and pull-apart basins within the Mananjary gold district. Moreover, the SSF structurally controlled the spatial distribution of Vohilava-Nosivolo and Maha groups. R Riedel shear faults appear as North North East – South South West faults. R’ Riedel shear faults occur in the north of the study area with East North East -West South West orientation. Tectonic block rotation occurred between Ampasinambo and Soavina. P’ shear faults striking West North West – East South East occur in Vohilava. Some folds are associated with the SSF as well. Vohilava positive flower structure which used to be a syncline and its antiform equivalent are SSF footprints. The latter was active since Mesoarchean.